Differences in postural stability between the athletes from various winter sports - Kolodziej, E.; Tchórzewski, D.; Jaworski, J. (Current Research in Motor Control, 2016)
The effect of body balance on the risk of injury in sport has been described extensively but the correlations between postural stability and sports performance remain unclear (Hrysomallis 2011). Previous findings have demonstrated that athletes have better ability to maintain balance compared to untrained controls (Schmit et al. 2005; Thorpe, Ebersole 2008). This means that the increased physical activity improves balance. It was also found that the ability to maintain balance is substantially correlated with the results of a series of special tests in different sports (Malliou et al. 2004). The use of balance exercises in training sessions led to the improvement in oriented and special fitness (Yaggie, Campbell 2006). Dynamic technological advances have promoted the development of the equipment designed based on balance boards, which allow not only for maintaining balance on an unstable ground but also for recording and modelling of the training session (Clark et al. 2010). A particular interest in such exercises is observed among coaches of winter sports, where balance is a key coordination ability while the technique requires abilities of conscious losing and regaining the state of instantaneous balance (Kawai et al. 2003; Yuda et al. 2007; Alpini et al. 2008; Platzer et al. 2009). The present study was aimed at determination how the training of specific winter sports (biathlon, Nordic combined, speed skating, cross-country skiing, ski jumping and Alpine skiing) have an effect on differences in the level of athlete stability. Two research questions were formulated: (1) Are there significant differences in the level of stability between athletes from sports were high balance skills are needed and (2) if yes, are these differences similar in both planes?